The bistable mitotic switch in fission yeast - Novák, Béla; Tyson, John J. (Molecular biology of the cell, 2024)
In favorable conditions, eukaryotic cells proceed irreversibly through the cell division cycle (G1-S-G2-M) in order to produce two daughter cells with the same number and identity of chromosomes of their progenitor. The integrity of this process is maintained by “checkpoints” that hold a cell at particular transition points of the cycle until all requisite events are completed. The crucial functions of these checkpoints seem to depend on irreversible bistability of the underlying checkpoint control systems. Bistability of cell cycle transitions has been confirmed experimentally in frog egg extracts, budding yeast cells and mammalian cells. For fission yeast cells, a recent paper by Patterson et al. (2021) provides experimental evidence for an abrupt transition from G2 phase into mitosis, and we show that these data are consistent with a stochastic model of a bistable switch governing the G2/M checkpoint. Interestingly, our model suggests that their experimental data could also be explained by a reversible/sigmoidal switch, and stochastic simulations confirm this supposition. We propose a simple modification of their experimental protocol that could provide convincing evidence for (or against) bistability of the G2/M transition in fission yeast. Based on their elegant experiments, Patterson et al. (2021) concluded that the G2/M transition in fission yeast is controlled by a bistable switch, but we question that conclusion. Using detailed stochastic simulations, we show that the coexisting low and high Cdk1 activity states observed by Patterson et al. can be reproduced by either an irreversible/bistable or a reversible/ultrasensitive switch, and our analysis shows why the experiments of Patterson et al. are inconclusive. We suggest a decisive experiment to distinguish unequivocally between an irreversible/bistable and a reversible/ultrasensitive switch.